2018
DOI: 10.1111/infa.12240
|View full text |Cite
|
Sign up to set email alerts
|

The Influence of Maternal Socialization on Infants’ Social Evaluation in Two Cultures

Abstract: Although a growing body of research has explored the early development of social evaluation, no research has directly compared social evaluations of infants between different cultures. In addition, there has been little understanding regarding socialization's effects on this ability. The goal of this study was to expand on earlier findings on social evaluation in infants by investigating a broader sample from two cultures, and to explore the influence of maternal socialization on infants’ social evaluation. Us… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
11
0

Year Published

2020
2020
2021
2021

Publication Types

Select...
5
2
1

Relationship

1
7

Authors

Journals

citations
Cited by 44 publications
(13 citation statements)
references
References 53 publications
2
11
0
Order By: Relevance
“…Cowell and Decety (2015) took into account interindividual differences by assessing toddlers' temperament and parents' disposition in perspective taking, but found neither of those factors to be related to toddlers' preference in the hill paradigm. Shimizu et al (2018) found that the number of mothers' socially evaluative comments, while watching the box and ball paradigms with their infants was associated with a higher likelihood of choosing the prosocial puppet in their children. Infants' sociomoral preference had been assessed before mothers watched the box and ball paradigms with their infants, to ensure that infants' choices were not influenced by having listened to their mothers' comments on the box and ball paradigm.…”
Section: The Role Of Empathy and Attachment In Toddlers' Sociomoral Preferencesmentioning
confidence: 93%
See 2 more Smart Citations
“…Cowell and Decety (2015) took into account interindividual differences by assessing toddlers' temperament and parents' disposition in perspective taking, but found neither of those factors to be related to toddlers' preference in the hill paradigm. Shimizu et al (2018) found that the number of mothers' socially evaluative comments, while watching the box and ball paradigms with their infants was associated with a higher likelihood of choosing the prosocial puppet in their children. Infants' sociomoral preference had been assessed before mothers watched the box and ball paradigms with their infants, to ensure that infants' choices were not influenced by having listened to their mothers' comments on the box and ball paradigm.…”
Section: The Role Of Empathy and Attachment In Toddlers' Sociomoral Preferencesmentioning
confidence: 93%
“…Shimizu et al. (2018) found that the number of mothers' socially evaluative comments, while watching the box and ball paradigms with their infants was associated with a higher likelihood of choosing the prosocial puppet in their children. Infants' sociomoral preference had been assessed before mothers watched the box and ball paradigms with their infants, to ensure that infants' choices were not influenced by having listened to their mothers' comments on the box and ball paradigm.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Families in the United States were recruited in Green Bay, Wisconsin, and Japanese families were recruited in Saitama, Japan. Infants and mothers came to the laboratory as part of an ongoing investigation focused on early social and cognitive development, which was reported elsewhere (Shimizu et al, 2018). All the U.S. infants and mothers were born in the United States and spoke English as their first language.…”
Section: Methodsmentioning
confidence: 99%
“…A similar lack of preference was documented by Nighbor et al [23] with 5-to 16-month-olds. Conversely, using the 'ball scenario', Scola et al [24] reported a significant preference for prosocial characters in 12-to 24-and 24-to 36-month-olds, whereas Shimizu et al [25] documented a similar, albeit weaker, preference in 15-to 18-month-olds, but not in younger age groups. It is worth noting, however, that previous replication attempts have followed the methods of the original studies to varying degrees of fidelity.…”
Section: Introductionmentioning
confidence: 97%